PRAGMALINGUISTIC FEATURES OF THE SPEECH ACT OF REPROACH IN ENGLISH - Mukhtorova, Mokhlaroyim (University Research Base, 2024)
This thesis investigates the pragmalinguistic features of the speech act of reproach in English, focusing on the linguistic strategies employed in expressing reproach and the sociocultural factors that influence these strategies. The findings reveal a spectrum of reproach strategies, emphasizing the role of context, power dynamics, and cultural background in shaping speakers' choices. Direct reproach tends to be used in hierarchical situations, while indirect reproach is favored in informal or equal-status interactions. The study highlights the significance of understanding reproach as a complex speech act influenced by various pragmatic and sociocultural factors, contributing to the fields of pragmatics and intercultural communication.